2006
DOI: 10.7547/0960226
|View full text |Cite
|
Sign up to set email alerts
|

Foot Pathology in Patients with Paget’s Disease of Bone

Abstract: The characteristic bone deformities associated with advanced Paget’s disease of bone may result in abnormal gait and plantar foot pressures, which contribute to the development of pressure-related skin problems. This study aimed to characterize the foot problems and foot-care needs in this patient group and to investigate the effect of disease distribution on the occurrence of foot pathology. One hundred thirty-four patients with Paget’s disease were assessed clinically, and the Foot Structure Index was comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Williams and Bowden [90] correlated high FFI scores to foot morbidity in rheumatic diseases, and estimated cost of care/staffing concerns for that patient subset. Williams [91] also used the FFI scores in patients with Paget's disease and noted the impacts on plantar foot pressures, gaits, and ambulation abilities. Kamanli et al [92] correlated the scores of the FFI and foot bone mineral density, then extrapolated these scores to that individual's skeletal bone density.…”
Section: Resultsmentioning
confidence: 99%
“…Williams and Bowden [90] correlated high FFI scores to foot morbidity in rheumatic diseases, and estimated cost of care/staffing concerns for that patient subset. Williams [91] also used the FFI scores in patients with Paget's disease and noted the impacts on plantar foot pressures, gaits, and ambulation abilities. Kamanli et al [92] correlated the scores of the FFI and foot bone mineral density, then extrapolated these scores to that individual's skeletal bone density.…”
Section: Resultsmentioning
confidence: 99%
“…These validity results were similar to those related studies that investigated variable dimensions. Moderate to high correlations were found with pain-VAS [17,20], function-VAS [17], physical and mental health status [17,20,45], activity scale [17] and health-related quality of life [15,46]. A study of a Spanish version FFI reported a moderate correlation of the questionnaire with the EQ-5D and with the pain-VAS and weak correlation with the 12-item short-form health survey (SF-12) [47].…”
Section: The Construct Validity and Criterion Validitymentioning
confidence: 99%
“…It has a relative high frequency in some populations but less than primary osteoporosis (7). Bone deformities as it might have been in this case are identified especially in pressure areas (8,9,10). Serum total alkaline phosphatase remains the first line of assays even less than on fifths of cases had normal values (5,10,11).…”
Section: Discussionmentioning
confidence: 55%